1988
DOI: 10.1128/mcb.8.8.3550
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protection against cold stress of Drosophila melanogaster.

Abstract: Heat shock protein synthesis can be induced during recovery from cold treatment of Drosophila melanogaster larvae. Survival of larvae after a cold treatment is dramatically improved by a mild heat shock just before the cold shock. The conditions which induce tolerance to cold are similar to those which confer tolerance to heat.Heat shock proteins are a group of proteins which are universally expressed in response to heat, heavy metals, and a variety of chemical treatments (1, 5, 10, 11). The major heat shock p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
3
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(98 citation statements)
references
References 9 publications
5
89
3
1
Order By: Relevance
“…Consistent with this view is mounting evidence that protein synthesis is important for both heat tolerance (Stephanou et al 1983) and cold tolerance (Burton et al 1988;Misener et al 2001) and that variation in hsr-omega influences both heat tolerance (McKechnie et al 1998;Rako et al 2007) and cold tolerance (Collinge et al 2008). While there is little doubt about the importance of variation in the hsps, particularly hsp70, in influencing thermal tolerance variation (Krebs and Feder 1997;Bettencourt et al 1999;Sørensen et al 2003), variation in hsr-omega via its effects on protein synthesis and its shutdown may also be an Omega-c relative to cyck Fig.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…Consistent with this view is mounting evidence that protein synthesis is important for both heat tolerance (Stephanou et al 1983) and cold tolerance (Burton et al 1988;Misener et al 2001) and that variation in hsr-omega influences both heat tolerance (McKechnie et al 1998;Rako et al 2007) and cold tolerance (Collinge et al 2008). While there is little doubt about the importance of variation in the hsps, particularly hsp70, in influencing thermal tolerance variation (Krebs and Feder 1997;Bettencourt et al 1999;Sørensen et al 2003), variation in hsr-omega via its effects on protein synthesis and its shutdown may also be an Omega-c relative to cyck Fig.…”
Section: Resultssupporting
confidence: 48%
“…In these studies the kinetics of protein synthesis that was assessed in ovarian tissues following a heat shock was associated with changes in the timing and extent of hsp production, with timing and extent of housekeeping protein shutdown, and with heat stress survival differences between the lines. While a few other studies have asked if protein synthesis relates to thermal tolerance (Dingley and MaynardSmith 1968;Burton et al 1988;Misener et al 2001), and considerable research has shown how hsps and their genes are up-regulated following thermal stress (Lis and Wu 1994;Yost et al 1990), little effort has been made to investigate the shutdown of general protein synthesis and how this impinges on hsp production and thermotolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, more than 50% of the P. megistus nymphs at different developmental phases survive for at least one month after a short cold shock (Garcia et al 1999b). While cryoprotectants are unknown in these insects, it is hypothesized that heat shock proteins (hsp) confer a certain amount of protection to P. megistus against cold in a similar way to that reported for some other insect species (Chen et al 1987, Burton et al 1988, Komatsu et al 1996. Indeed, cold tolerance may be induced in P. megistus (Garcia et al 1999a).…”
mentioning
confidence: 77%
“…Based on data for other insect species, it is hypothesized that hsp synthesis may also be engaged in a certain protection of P. megistus organism against protein abnormalities resulting from the cold shock, mainly when it did not extend for very long periods of time and affected fully nourished specimens (Chen et al 1987, Burton et al 1988, Komatsu et al 1996.…”
Section: Discussionmentioning
confidence: 99%